Simmel über die präsuppositionellen und epistemischen Ebenen von Analyse und Theoriebildung in der Soziologie - de Farias, Alberto Luis Cordeiro (Simmel Studies)

(untitled) (Edizioni ETS, 2024)
Drawing on selected passages from Simmel's texts, this article seeks to, on one hand, consolidate the key elements of his understanding of the presuppositional level in sociology, and on the other hand, building on insights particularly evident in an essay published in the late 19th century, to develop a complementary second level of analysis and theorization in sociology, which I term the epistemic level. Thus, in the first part of the text, with an emphasis on Philosophie des Geldes and Soziologie, I address Simmel's understanding of the presuppositional elements in social-theoretical reflection on the world, seeking to determine the content of this level of analysis and theorizing in the transition from philosophy to the particular sciences. Secondly, I turn to the definition of the epistemic level in Simmel. At this point, I focus on delineating the fundamental questions of a historical-systematic nature that can be explored from this epistemic level. I conclude with some general considerations about the theoretical significance of these levels for sociological analysis and theorizing.